ASSESSING THE INFLUENCE OF THE ISLAMIC FINANCIAL SYSTEM ON INDONESIA'S ECONOMIC GROWTH IN THE LONG AND SHORT RUN FROM 2011 TO 2022 - Kamarni, Neng; Andrianus, Fery; Dhoifullah, Aisyah (Economic and Science Faculty of Islamic State University, 2023)
This study aims to see the performance of the Islamic financial system on Indonesia's economic growth in the long and short run from 2011 to 2022. The research method uses the Autoregressive Distributed Lag (ARDL) analysis method. The data used in this study are secondary. Secondary data is a source of data that is not directly obtained from objects through interviews. Secondary data can be obtained from other organizations or individuals such as census data collected. Data from the Indonesian Central Bureau of Statistics (BPS) and the Financial Services Authority (OJK). This study uses economic growth as the dependent variable and the Indonesian Sharia Stock Index and Islamic banking financing as independent variables. The research provides results that the performance of Islamic banking financing and the Indonesian Sharia Stock Index provides positive and significant results on economic growth. Based on the results of this study, it is hoped that the government will further strengthen policies that focus on the development of Islamic finance in Indonesia because improving the performance of the Islamic financial system can improve and encourage economic growth in Indonesia.